Glosa do postanowienia Sądu Najwyższego z dnia 13 kwietnia 2005 r., sygn. III KK 23/05 - Wróbel, Adam (Studia Iuridica Toruniensia, 2013)
<!--[if gte mso 9]> <![endif]--> The Supreme Court in commented decision claims, that the worker within the meaning of art. 220 § 1 c.c. is a worker within the meaning of the labour law provisions (a person who is specified in art. 2 l.c. as well as art. 22 l.c.). The author share this point of view, and gives additional arguments supporting this thesis; he shares an opinion, that in omission crimes, specific legal duty to prevent the negative effect of crime (in consequential crimes), may come from the decrees to the acts; the author claims – regardless of the above – that this duty may come from some other legal acts. <!--[if gte mso 9]> Normal 0 21 false false false PL X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->